Synthetic charts to control bivariate processes with autocorrelated data - Simões, Felipe Domingues [UNESP]; Leoni, Roberto Campos [UNESP]; MacHado, Marcela Aparecida Guerreiro [UNESP]; Costa, Antonio Fernando Branco [UNESP] (Elsevier, 2016)
In this study, we propose the use of simultaneous Xcharts to control bivariate processes with autocorrelated data. The first set of Xcharts is side-sensitive with regard to the same variable (SV Xcharts) and the second one is side-sensitive with regard to both variables (BV Xcharts). The Markov chain approach was used to obtain the steady-state properties of the Xcharts. In comparison with the standard synthetic T2 chart, the SV and the BV charts signal faster in a wide variety of disturbances, except when the variables are high correlated. The BV charts are simpler and signal faster than the SV charts.
Keywords: Bivariate process; Side-sensitive; Steady state; Synthetic; X charts